Peran Perempuan dalam Politik menurut Yusuf Al-Qardhawi - Asif Trisnani; Wenning Windiarti; Hidayatus Sa'adah (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2021)
Today women in the political stage are actually not a stranger in the world since ancient times. The direct or indirect role of women has its own influence. The discourse of women's involvement in politics by providing a 30% quota, is still a controversial discourse, as well as other gender equality issues. In essence, women and men have the same rights and obligations in law and government, as stated in article 27 paragraph 1 UUD 1945.Many women refuse by limiting women's steps. One view states that women should stay at home, serve their husbands, and only have a domestic role and should not be involved in politics. This view is reinforced by the fuqaha. The famous contemporary scholar of this century Yusuf Al-Qardhawi who has different views and opinions on the involvement of women in politicsHe sees that the above argument is not only textual, but the context must also be considered and considers men and women to be a mukallaf, required to worship Allah, uphold religion, carry out obligations, perform amar ma'ruf nahi munkar, have the same rights to choose and be elected, so that there is no strong argument for the prohibition of women from participating in politicsAl-Qardhawi allows women to carry out social roles as judges with some special terms and conditions. Because according to him, this position does not conflict with social interests. On the contrary, social interests actually require the involvement of women. With this, it can be said that the fatwa above emerged due to socio-political influences. In this case, al-Qardhawi is moderate. Whereas in the matter of the president, the representative council is not at all identical with the leadership of a caliph or amirul mu'minin who is individual but the leadership of the president, the representative council that is currently developing is collective, not individual.